Pengaruh Career Development, Self-Efficacy Terhadap Turnover Intention Yang Dimediasi Oleh Organizational Commitment di PT. XYZ - Yatin Rosid; Nur Fauzan Iskandar; Rini Rohayani; Retno Purwani Setyaningrum (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
This study was conducted at PT XYZ to identify the relationship between career development, self-efficacy, organizational commitment, and turnover intention. Turnover that occurred in the period April 2024 - March 2025 can disrupt the company's performance. The purpose of this study is to determine the main factors causing turnover. Data were analyzed using Partial Least Square (PLS) with the Structural Equality Model (SEM) technique through SmartPLS 4.1.1.1 software to evaluate validity, reliability, and relationships between variables. The sample was 98 employees from 130 employees at PT XYZ, and the Solvin formula was used to determine the sample size with a 5% error tolerance level or 0.05. The results of the study found that Career development influences organizational commitment and turnover intention with P values of 0.000 and 0.023, self-efficacy influences organizational commitment and turnover intention with P values of 0.000 and 0.001, and career development influences turnover intention through organizational commitment with P value of 0.007, and self-efficacy influences turnover intention through organizational commitment with P value of 0.000. The findings show that Organizational Commitment can mediate the relationship between Career Development, Self-Efficacy and Turnover Intention at PT XYZ, companies need to increase employee commitment by conducting more intensive training and creating a communication forum between the organization and employees.